Fecal Antibodies to Cryptosporidium parvum in Healthy Volunteers - Dann, Sara M. (American Society for Microbiology, 2000)
This study examined the intestinal antibody response in 26 healthy volunteers challenged with Cryptosporidium parvum oocysts. Fecal extracts were assayed for total secretory immunoglobulin A (IgA) and C. parvum-specific IgA reactivity. Specific IgA reactivity was standardized to IgA concentration and expressed as a reactivity index (RI). Anti-C. parvum fecal IgA (fIgA) increased significantly in 17 of 26 (65.4%) following oocyst ingestion. Of those with detectable responses, 59, 76.5, and 94.1% were positive by days 7, 14, and 30, respectively. Volunteers receiving high challenge doses (>1,000 and 300 to 500 oocysts) had higher RIs (RI = 5.57 [P = 0.027] and RI = 1.68 [P = 0.039], respectively) than those ingesting low doses (30 to 100 oocysts; RI = 0.146). Subjects shedding oocysts and experiencing a diarrheal illness had the highest fIgA reactivity. When evaluated separately, oocyst excretion was associated with an increased fIgA response compared to nonshedders (RI = 1.679 versus 0.024, respectively; P = 0.003). However, in subjects experiencing diarrhea with or without oocyst shedding, a trend toward a higher RI (P = 0.065) was seen. Extracts positive for fecal IgA were further examined for IgA subclass. The majority of stools contained both IgA1 and IgA2, and the relative proportions did not change following challenge. Also, no C. parvum-specific IgM or IgG was detected in fecal extracts. Thus, fecal IgA to C. parvum antigens was highly associated with infection in subjects who had no evidence of previous exposure and may provide a useful tool in detecting recent infections.